Justice in Tort Law of Russia and China - V. Dolinskaya; T. Letuta (BRICS Law Journal)
The article describes the main issues of tort liability regulation in the context of the principle of justice and its implementation into the legislation and law enforcement practice of the Russian Federation and the People’s Republic of China (PRC). The comparative method of the study revealed critical differences in the provisions of Russian and Chinese tort law. The analysis of the domestic and foreign scientists’ works and judicial practice in disputes on compensation for harm contributed to findings and results related to the forms of justice implementation in these countries. The authors argue the dominance of procedural form of justice implementation in the Russian legal system but distributive form in the Chinese legal system. Positive and negative aspects of both forms are discussed. The reform of Chinese civil law which completely changed legal regulation of tort liability and excluded many of the controversial provisions of the previous PRC law on liability for offenses required new theoretical studies aimed at evaluating new laws. Comparison of the new tort law of the People’s Republic of China and the tort law of the Russian Federation is especially acute in connection with the objective to integrate the BRICS member countries against the background of the increasing conflicts in international arena. Optimization of legal norms by choosing the most effective model for the principle of justice would improve the protection of victims’ rights. In particular, the authors conclude that it is necessary to integrate the Russian and Chinese approach for determining the compensation and defining clear criteria for resolving disputes. In addition, possibility of the tort liability parties to agree on the procedure, time frame and amount of compensation should be set out under the law.